(untitled) (Journal of Science and Technology, 2016)
Homogenized pastes were prepared by adding top-bond white glue as binder to natural fibrous material prepared out of different proportions of bamboo (Ozizentera arbonica), coconut husk (Cocus nucifera<.i>), sponge (Acanthus montanus) and wood (cordial). Test samples were prepared from dried cast samples for creep and hardness tests. The results of the analysis were used to determine the material that has close properties to the commercially sourced gasket used as control. The overall assessment of the compatibility and suitability tests confirmed the possible applicability of the materials as gasket in fuel pump, carburetors and in engine oil pumps. The locally produced materials have been tested and found suitable as substitute to the conventional material in this order: Coconut husk mixed with sponge (Ch+Sp) in uniform proportion; Coconut husk (Ch) alone without any mixture, and the mixture of the four fibres (Ba+Ch+Sp+Wd).